Can Dynamic MRI Be Used to Accurately Identify Velopharyngeal Closure Patterns?. (April 2018) - Perry, Jamie L.; Mason, Kazlin; Sutton, Bradley P.; Kuehn, David P.
Background: Dynamic magnetic resonance imaging (MRI) has been proposed as a non-invasive, child-friendly, reproducible, and repeatable imaging method providing a 3-dimensional view of the velopharyngeal structures and function during speech. However, the value of dynamic MRI as compared to imaging methods such as nasopharyngoscopy is not well understood. The aim of this study was to compare the ability of nasopharyngoscopy and dynamic MRI to accurately identify velopharyngeal closure patterns among adults without cleft palate. Methods: Participants included 34 healthy adults with normal anatomy between 19 and 33 years of age (mean = 23 years; SD = 4.1 years). Participants underwent dynamic MRI and nasopharyngoscopy studies and comparisons were performed to determine the intra- and inter-rater reliability for accurately determining closure pattern. The MRI acquisition was a dynamic acquisition of a 2D plane. Results: Strong inter- (κ = .824; P < .001) and intra-rater (Rater 1: κ = 0.879, P < .001, 94% agreement between ratings; Rater 2 with 100% agreement) agreement was observed for the identification of closure pattern using nasopharyngoscopy. Inter-rater agreement for ratings using MRI demonstrated moderate agreement (κ = .489; P < .004). Examining point agreement revealed only 27 of the 33 ratings of MRI showed agreement (80%). Conclusion: This demonstrates that inter-rater reliability for determining closure patterns from nasopharyngoscopy is good; however, ratings using MRI was less reliable at determining closure patterns. It is likely that future improvements in dynamic imaging with MRI to enable 3D visualizations are needed for improved diagnostic accuracy for assessing velopharyngeal closure patterns.